UNVEILING THE HIDDEN IMPACT OF GREEN ACCOUNTING ON CORPORATE SUCCESS - Tullah, Dewi Sarifah; Febrian, Jan; Novianto, Fajar; Jason, Jason; Khairunnisa, Hana (Kesatuan Press, 2025)
Increasing stakeholder demand has driven firms to integrate environmental sustainability into their business strategies. Green accounting, encompassing environmental performance and green investment, has become a key approach to achieving these goals. This study examines the effect of green accounting on financial performance, with Corporate Social Responsibility (CSR) as a moderating variable. Multiple linear regression analysis was conducted using quantitative data from financial and sustainability reports of publicly traded Indonesian firms (2021–2023). The findings indicate that environmental performance significantly enhances financial performance by improving legitimacy and operational efficiency. However, green investment does not directly influence financial performance, nor does CSR moderate it. While CSR independently strengthens financial performance, its moderating role in environmental performance negatively impacts short-term financial results, suggesting that CSR costs may outweigh immediate benefits. The study underscores the need for firms to optimize cost management and effectively communicate sustainability efforts to enhance stakeholder trust and long-term financial performance.